Saliva and wastewater surveillance for SARS-CoV-2 during school reopening amid COVID-19 pandemic in Thailand - Laor Nakgul; Ekawat Pasomsub; Supranee Thongpradit; Suwannee Chanprasertyothin; Somsak Prasongtanakij; Kunlawat Thadanipon; Chokchai Jadmuang; Daranee Kunanan; Boonsong Ongphiphadhanakul; Angsana Phuphuakrat (Elsevier, 2023)
Objectives: School closure during the coronavirus disease 2019 (COVID-19) pandemic resulted in a negative impact on children. Serial testing of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been proposed as a measure for safety school reopening. We aimed to study the usefulness of SARS-CoV-2 surveillance by saliva testing and performing wastewater surveillance for SARS-CoV-2 in a day school in a resource-limited setting. Methods: We conducted a cluster randomized study to investigate the potential use of saliva antigen testing compared to saliva pooling for nucleic acid detection in a primary school in Thailand from December 2021 to March 2022. Wastewater surveillance in the school was also performed. Results: A total of 484 participants attended the study. SARS-CoV-2 was detected in two participants from the tests provided by the study (one in the pool nucleic acid test arm, and another in the quantitative antigen test arm). Additional ten participants reported positive results on an additional rapid antigen test (RAT) performed by nasal swab when they had symptoms or household contact. There was no difference among arms in viral detection by intention-to-treat and per protocol analysis (p = 0.304 and 0.894, respectively). We also investigated the feasibility of wastewater surveillance to detect the virus in this setting. However, wastewater surveillance could not detect the virus. Conclusions: In a low COVID-19 prevalence, serial saliva testing and wastewater surveillance for SARS-CoV-2 rarely detected the virus in a day school setting. Performing RAT on nasal swabs when students, teachers or staff have symptoms or household contact might be more reasonable.